Incremental Prognostic Value of the Incorporation of Clinical Data Into Coronary Anatomy Data in Acute Coronary Syndromes: SYNTAX-GRACE Score - Viana,Mateus dos Santos (2017)
Abstract Background: When performing coronary angiography in patients with acute coronary syndrome (ACS), the anatomical extent of coronary disease usually prevails in the prognostic reasoning. It has not yet been proven if clinical data should be accounted for in risk stratification together with anatomical data. Objective: To test the hypothesis that clinical data increment the prognostic value of anatomical data in patients with ACS. Methods: Patients admitted with objective criteria for ACS and who underwent angiography during hospitalization were included. Primary outcome was defined as in-hospital cardiovascular death, and the prognostic value of the SYNTAX Score (anatomical data) was compared to that of the SYNTAX-GRACE Score, which resulted from the incorporation of the GRACE Score into the SYNTAX score. The Integrated Discrimination Improvement (IDI) was calculated to evaluate the SYNTAX-GRACE Score ability to correctly reclassify information from the traditional SYNTAX model. Results: This study assessed 365 patients (mean age, 64 ± 14 years; 58% male). In-hospital cardiovascular mortality was 4.4%, and the SYNTAX Score was a predictor of that outcome with a C-statistic of 0.81 (95% CI: 0.70 - 0.92; p < 0.001). The GRACE Score was a predictor of in-hospital cardiac death independently of the SYNTAX Score (p < 0.001, logistic regression). After incorporation into the predictive model, the GRACE Score increased the discrimination capacity of the SYNTAX Score from 0.81 to 0.92 (95% CI: 0.87 - 0.96; p = 0.04). Conclusion: In patients with ACS, clinical data complement the prognostic value of coronary anatomy. Risk stratification should be based on the clinical-anatomical paradigm, rather than on angiographic data only.